From womb to world: mapping gut microbiota-related health literacy among Italian mothers, a cross-sectional study - Alessandra Consales; Letizia Toscano; Chiara Ceriotti; Valentina Tiraferri; Silvana Castaldi; Maria Lorella Giannì (BMC, 2024)
Abstract Background The gut microbiota is a key determinant of long-term health. Promoting maternal health literacy may enhance children well-being. Aim of the present study was to assess gut microbiota-related health literacy of Italian women and identify potential gaps in awareness. Methods A cross-sectional survey study was conducted using an online questionnaire (17 questions) on determinants and long-term impact of infant gut microbiota. The survey targeted Italian pregnant women and mothers of children under 2 years old, and was distributed through various social media channels between September 28th and November 15th, 2022. A total score was calculated as the sum of positive answers. Data on demographics, pregnancy status, and pre-existing knowledge of the infant gut microbiota were also collected. Descriptive and inferential statistics were applied. Results The questionnaire was completed by 1076 women. Median total score was 9 [7-11]. The 81.7% of respondents declared prior knowledge of the gut microbiota. The internet was among the most commonly cited primary sources of information. Independent predictors of total score were having a university degree (B = 0.656, p = 0.002) and prior knowledge (B = 2.246, p < 0.001). Conversely, older age was associated with lower total scores (B = -0.092, p < 0.001). The least known determinants of infant gut microbiota were gestational BMI, prematurity, mode of delivery and NICU stay. Pregnant women failed to recognize the role of breastfeeding in the development of infant gut microbiota more frequently than non-pregnant women. The 97.5% of participants reported increased interest in the gut microbiota, with heightened interest associated with prior knowledge. Conclusions Our study revealed a moderate level of knowledge about infant gut microbiota among respondents, emphasizing the positive impact of prior knowledge on understanding and interest. Targeted educational interventions are needed to address awareness gaps, especially concerning the influence of breastfeeding on infant gut microbiota. Healthcare providers have the potential to enhance women's knowledge and awareness of this topic.